Original articleCabergoline protects dopaminergic neurons against rotenone-induced cell death in primary mesencephalic cell culture - Meinel, Jörn; Radad, Khaled; Rausch, Wolf-Dieter; Reichmann, Heinz; Gille, Gabriele (Folia Neuropathologica, 2015)
In the present study, primary mesencephalic cell cultures prepared from embryonic mouse mesencephala were used to investigate the neuroprotective effect of cabergoline, an ergoline D2 receptor agonist, against the pesticide and neurotoxin rotenone relevant to Parkinson disease (PD). Treatment of cultures with cabergoline alone significantly increased the number of tyrosine hydroxylase immunoreactive (THir) neurons and reduced the release of lactate dehydrogenase (LDH) into the culture medium compared to untreated controls. Against rotenone toxicity, cabergoline significantly rescued degenerating THir neurons, reduced the release of LDH into the culture medium and improved the morphology of surviving THir neurons. The neuroprotective effects afforded by cabergoline were independent of dopaminergic stimulation as blocking of dopamine receptors by the dopamine receptor antagonist sulpiride did not prevent them. Furthermore, rotenone-induced formation of reactive oxygen species (ROS) was significantly reduced by cabergoline. Although cabergoline increased the glutathione (GSH) content in the culture, the protective effect for dopaminergic neurons seemed not to be predominantly mediated by increasing GSH, as depletion of GSH by L-buthionine-(S,R)-sulfoximine (BSO), a GSH biosynthesis inhibitor, did not prevent cabergoline-mediated neuroprotection of THir neurons in rotenone-treated cultures. Moreover, cabergoline significantly increased the ATP/protein ratio in primary mesencephalic cell cultures when added alone or prior to rotenone treatment. These results indicate a neuroprotective effect of cabergoline for dopaminergic neurons against rotenone toxicity. This effect was independent of dopamine receptor stimulation and was at least partially mediated by reducing ROS production and increasing the ATP/protein ratio.